2012
DOI: 10.1159/000339935
|View full text |Cite
|
Sign up to set email alerts
|

Superimposed Preeclampsia in Women with Chronic Kidney Disease

Abstract: Aim: To evaluate whether pregnant women with chronic kidney disease (CKD) adapt poorly to increases in renal blood flow. This can exacerbate renal function and impair perinatal outcome, as there is a major interplay between CKD and preeclampsia (PE). Methods: We analyzed the outcomes of 90 pregnant women with preexisting CKD. The estimated glomerular filtration rate (eGFR) was measured along with the levels of angiogenic factors, soluble fms-like tyrosine kinase 1 (sFlt-1) and placental growth factor, which mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…In several previous studies [5,6,22], patients with PE were found to have an increased peroxidation substrate level in their serum when compared with normal pregnant women. There was a twofold increase in TG and free fatty acid content, while the amount of HDL synthesized declined tremendously and the amount of lipid peroxidase in HDL increased significantly.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In several previous studies [5,6,22], patients with PE were found to have an increased peroxidation substrate level in their serum when compared with normal pregnant women. There was a twofold increase in TG and free fatty acid content, while the amount of HDL synthesized declined tremendously and the amount of lipid peroxidase in HDL increased significantly.…”
Section: Discussionmentioning
confidence: 98%
“…Although a key issue in obstetrics, the etiology and pathogenesis of PE have not yet been fully elucidated, making the prevention and the treatment of this disease difficult [4]. A number of studies have reported the prevalence of lipid metabolism disorder in patients with PE [5,6]. Lipid peroxidation has been shown to damage vascular endothelial cells and is associated with acute atherosclerosis in uterine spiral arteries and placental bed arterioles, resulting in stenosis and increased vascular resistance of uterine spiral arteries [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the incorporation of angiogenic markers may help to risk stratify women with high suspicion for preeclampsia. Similarly, angiogenic markers have proved to be useful in distinguishing between confounding diagnoses, such as chronic hypertension, CKD, and lupus nephritis (12)(13)(14)(15). The potential to target sFlt as a therapy is also exciting and currently being studied using an apheresis technique (16).…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…Interestingly, none of the societies address this issue in their guidelines. However, the angiogenic markers (as mentioned above in Angiogenic Factors) sFlt-1 and PlGF have been shown to be able to distinguish preeclampsia from CKD (13,14) and thus, may be potentially incorporated in practice for more clarity.…”
Section: Guidelinesmentioning
confidence: 99%
“…The reason for excluding cesarean section was to form a more uniform cohort of very low risk parturient women with minimal obstetric intervention. Complications of pregnancy were defined as serious problems that are associated with pregnancy such as hypertensive disorders, preeclampsia [10], gestational diabetes, thromboembolic events, hyperthyroidism [11], etc. Complications of pregnancy were not exclusion criteria but rather their presence precluded inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%